Competencias ciudadanas: obstáculos de implementación para su consolidación como herramienta para reducir la violencia juvenil (2020)
This document seeks to identify the implementation obstacles faced by the Programa de Competencias Ciudadanas - PCC (Citizenship Skills Program) during its process of consolidation as an effective tool of public policy indicated to address the social problem of youth violence in Colombia. It presents as well, a series of recommendations for decision makers, which are meant to help reducing the gap between the plan and the work delivered by the PCC. A description of the youth violence problem and the performance of eleventh grade students in the section of social and citizenship skills of the Saber test in Colombia, Barranquilla and Cartagena is provided as contextualization; Likewise, In order to identify the implementation obstacles of the PCC, several interviews were conducted with two experts involved in the formulation of the program and six teachers of social sciences in two schools sponsored by the Pies Descalzos Foundation, located in the cities of interest. The information analysis resulted in the identification of nine implementation obstacles: i) A lack of clarity in fundamental concepts of the PCC, ii) the contextual violence faced by the students, iii) The low political gain of the program, iv) neglected importance of citizenship skills within the educational process of the students, v) A lack of resources, vi) the perception of educators about the PCC as an imposition from the government, vii) communication failures between formulators and implementers, viii) the program's non-mainstreaming and ix ) inadequate teacher training in terms of civic education. For each of the obstacles, a recommendation is presented, all of them aiming to mitigate the negative impact on the achievement of the program's objectives.